A Companion to British-Jewish Theatre since the 1950s, Jeanette R. Malkin, Eckart Voigts and Sarah Jane Ablett (Eds) (2021). (1st November 2021) - Mitschke, Samantha
Review of: A Companion to British-Jewish Theatre since the 1950s, Jeanette R. Malkin, Eckart Voigts and Sarah Jane Ablett (Eds) (2021)London: Bloomsbury, 272 pp., ISBN 978-1-35013-597-0, e-book, £76.50ISBN 978-1-35013-596-3, h/bk, £85.00